Kader Kesehatan Sebagai Konselor Gizi Anak - Septikasari, Majestika (Universitas Muhammadiyah Surabaya, 2018)
Lack of adequate nutrition intake not only affects the disruption of growth and development of children but can further impact on increased risk of morbidity and mortality of children. In 2016, the number of children under five in Slarang Village is 1056 toddlers and 63 (5.96%) of them are malnourished. One of the efforts to overcome the problem is through the role of health cadres. But with the number of Poyandu 11 Posyandu and 55 health cadres, the role of cadres in promotive efforts is still lacking. Observations conducted at 4 posyandu showed that the cadres were only responsible for recording and weighing. Based on the interviews, the cadres found that children's nutrition knowledge is still lacking, they can not counsel properly and there is no cadre handbook.Community service activities have been implemented with the results have been compiled pocket book nutrition cadres. The number of participants was 19 cadres, the cadre's knowledge about children's nutrition had increased from 61,8 average to 93,7 and had been monitored activity to see the cadre skill in giving nutrition counseling of children through visit to 6 posyandu where 11 cadres conducted skill evaluation nutritional counseling of children with a checklist of more than 70.Â Â Â